DIFFERENTIATED APPROACH TO THE TREATMENT OF NASAL OBSTRUCTION SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Nasal breathing is an important physiological process that causes air to enter the body. The air flow вдыхае inhaled through the nasal cavity experiences resistance from its structures: approximately 1/3 of the resistance ходитсяis applied to the movable part of the septum, the remaining 2/3 - to the area of the nasal valve. The resistance of the nose to air flow is due to various factors. First of all, the degree of nasal resistance depends on the vessels of the lower nasal concha. When blood stagnates in the cavernous venous plexuses, the shells swell and increase in size, which leads to narrowing of the nasal valve passage, sometimes to complete obstruction of the nasal cavity.